Formulation and evaluation of antibacterial activity of nanoparticles ointment preparation using Blimbi extract - Nia Lisnawati; Shirly Kumala; Deni Rahmat (Mazandaran University of Medical Sciences, 2018)
Indonesia has various beneficial plant species which have not been cultivated well yet. Blimbi (Averrhoa bilimbi L.) is among those plants which have antibacterial activities against Staphylococcus aureus and Escherichia coli. As carriers, the nanoparticles of this plant dissolve, trap, encapsulate, and attach the chemical preparation inside its matrix. This study aimed to compare the effect of two forms of the nanoparticles using Blimbi extract (i.e., single state and ointment preparation) on the antibacterial activity against bacteria. In this experimental study, the Blimbi extract changed to nanoparticles followed by a drying process using a drier spray. Afterwards, the nanoparticles were tested for antibacterial activity and mixed with an ointment base. The Blimbi extract was formulated in a form of absorbent ointment preparation with dark brown color and unique fragrance with pH of 6.42-6.80 and spread ability of 6.16-6.90 mm. According to the results, the diameters of the inhibition zone of nanoparticles using Blimbi extract on S. aureus and E. coli were 20 and 19.75 mm, respectively. The nanoparticles levels were higher in E. coli (12.25 mm) than those in S. aureus (15.50 mm). Meanwhile, the nanoparticles levels in ointment preparation were 15.84 and 14.73 mm for S. aureus and E. coli. The nanoparticles using Blimbi extract and the ointment using Blimbi extract were safe and did not irritate the skin.